Perceived Medical, Social, and Psychological Issues due to the COVID-19 Pandemic among Elderly: A Descriptive Analysis - Juneja, Khushboo; Kapoor, Kathan; Kumar, Ashwini; Eshwari, Kundangar; Rao S, Raghavendra; Mallya, Sneha Deepak (Indian Journal of Community Health, 2024)
Elderly individuals are more likely to suffer from both short and long-term consequences of COVID19, including exacerbation of existing illnesses, psychological issues, and increased risk of death. This study aimed to understand the medical, perceived psychological, and social health problems faced by the elderly due to the COVID-19 pandemic. This hospital-based study included 225 elderly patients (aged ?60 years) with chronic health conditions. Hypertension (70.2%) and diabetes mellitus (64.0%) were the most common morbidities among the study participants. At least 34.7% of the participants had one or more symptoms suggestive of psychological problems due to COVID-19 pandemic. Among the participants, 56.9% had difficulty with routine activities, 10.2% had trouble accessing medications and 8% faced issues in receiving routine medical care. There is a need to protect the interests of the elderly and suggest potential preventive measures and solutions for their medical, social and psychological problems.